(untitled) (Research, Society and Development, 2021)
Long Stay Institutions for the Elderly (LTCI) offer comprehensive care and support for individuals who need specialized care and cannot be assisted by their own family. However, during the covid-19 pandemic, these environments proved to be "easy targets" for the new coronavirus and, therefore, required a rapid response and adaptation from the entire healthcare team. The main objective of this study was to identify changes in nursing care for the elderly in LSIE during the coronavirus pandemic. This is a descriptive research, with a search for articles carried out in digital libraries. The studies analyzed indicated that the patients presented different clinical conditions, such as the appearance of physical and mental symptoms, to a lesser or greater degree. The nurse, as the main member of the LSIE management system, helps to coordinate the implementation of care measures, with the purpose of promoting health, preventing, and controlling the spread of the virus. It is up to the nurse to adopt strategies to reduce the risk of infection and mortality. The enormous challenges faced by these professionals in implementing prevention and care measures against a little-known disease at that time and in such a short time are evident. It was found that the greater the training and organization of nursing staff care, the better the results obtained in the safety of care for the elderly population and that nurses need to be prepared to act in different situations, even in emergencies.